Relationship Of Youth Knowledge And Attitude With Drug Abuse Prevention Efforts In Padang 29 Private Vocational School, 2017 - Andika, Mira (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
UNODC in the World Drug Report states that in 2010 there were 230 million people or 5% of the world's population aged 10-64 misusing drugs. Cannabis is the most widely used substance that is between 119 million - 224 million, 13% of injecting drug users have contracted HIV (14.6%). The purpose of research to know the relationship of knowledge and attitude of an adolescent with the effort of prevention of drug abuse in SMPN 29 Padang. The study used an analytic survey with a cross-sectional study design carried out at SMPN 29 Padang on June 17, 2017. The student's population of SMPN 29 Padang from class VII and VIII were 570 people with a sample size of 84 people. Results 63.1% of respondents have a high knowledge, 51.2% of respondents have a positive attitude, 60.7% of respondents have good drug abuse prevention efforts. There is a relationship between adolescent knowledge with the effort of prevention of drug abuse (p-value = 0,000) and there is a correlation between adolescent attitude with the effort of preventing drug abuse in SMPN 29 Padang (p-value = 0,030).